The importance of formal and informal support networks for foster parents in establishing the normalisation of children’s life - Horvat, Gordana (Socialno delo, 2023)
Foster care has become the focus of social work in Croatia in recent years, due to the lack of placement capacity in institutions and process of deinstitutionalisation which aims to achieve normalisation of human life in the community. In foster care, the normalisation of a child’s life is a challenge for all those involved in the process, as there is no inclusive model of foster care in Croatia and the role of social work is divided between all actors in the foster care process. Therefore, the thesis is put forward that for the establishment of the normalisation of the life of a foster child, it is important to provide formal and informal networks in the community, which are built and connected by social work in joint collaboration. The purpose of this paper is to identify the current support network for foster care, determine the needs of foster parents for normalizing the life of a child in foster care, and examine how social work as a profession contributes to this process. Through a qualitative analysis of eight semi-structured interviews with foster families conducted between November 2021 and January 2022, the findings indicate that foster parents need more accessible ongoing institutional support from social workers, but also non-formal forms of support, particularly associations of foster parents in the civil sector and better collaboration with children’s primary families.
Keywords: centri za socialno delo; childcare; deinstitucionalizacija; deinstitutionalisation; družina; families; foster care; otroško varstvo; rejništvo; social work; social work centres; socialno delo